Extraintestinal Manifestations of Inflammatory Bowel Disease. Issue 8 (August 2015) - Vavricka, Stephan R.; Schoepfer, Alain; Scharl, Michael; Lakatos, Peter L.; Navarini, Alexander; Rogler, Gerhard
Abstract : Abstract: Extraintestinal manifestations (EIM) in inflammatory bowel disease (IBD) are frequent and may occur before or after IBD diagnosis. EIM may impact the quality of life for patients with IBD significantly requiring specific treatment depending on the affected organ(s). They most frequently affect joints, skin, or eyes, but can also less frequently involve other organs such as liver, lungs, or pancreas. Certain EIM, such as peripheral arthritis, oral aphthous ulcers, episcleritis, or erythema nodosum, are frequently associated with active intestinal inflammation and usually improve by treatment of the intestinal activity. Other EIM, such as uveitis or ankylosing spondylitis, usually occur independent of intestinal inflammatory activity. For other not so rare EIM, such as pyoderma gangrenosum and primary sclerosing cholangitis, the association with the activity of the underlying IBD is unclear. Successful therapy of EIM is essential for improving quality of life of patients with IBD. Besides other options, tumor necrosis factor antibody therapy is an important therapy for EIM in patients with IBD. Abstract : Article first published online 2 July 2015